-3b+7(-b-4)=-88

Simple and best practice solution for -3b+7(-b-4)=-88 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3b+7(-b-4)=-88 equation:


Simplifying
-3b + 7(-1b + -4) = -88

Reorder the terms:
-3b + 7(-4 + -1b) = -88
-3b + (-4 * 7 + -1b * 7) = -88
-3b + (-28 + -7b) = -88

Reorder the terms:
-28 + -3b + -7b = -88

Combine like terms: -3b + -7b = -10b
-28 + -10b = -88

Solving
-28 + -10b = -88

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '28' to each side of the equation.
-28 + 28 + -10b = -88 + 28

Combine like terms: -28 + 28 = 0
0 + -10b = -88 + 28
-10b = -88 + 28

Combine like terms: -88 + 28 = -60
-10b = -60

Divide each side by '-10'.
b = 6

Simplifying
b = 6

See similar equations:

| 0.1p-0.2p=-6.6 | | -6n-2=22 | | 5x+48y+50=180 | | 12+(5x+1)=(18x-6) | | 98=-6-8n | | 55.50x+400=2000 | | 12+(5x+1)=((9x-3)*2) | | 7.00h+2.00h=58.50 | | x^2-2x-7=2cosx | | 5=2x+b+4 | | (5x+1)+19=(9x-3) | | 5+3-8+4+x=7 | | 18=8+5u | | 3x-5(x-5)=-3+4x+10 | | 24=m+60 | | -5.46+x=-.3 | | -4(3x+7)=-76 | | x^2-4x-7=3cosx | | 196x=196 | | 7x/3=35 | | 2/3×-7=4×-8 | | -2y+9=-27 | | 2x-51=19 | | -3+6x=67-4 | | (3x+11)+(10x-12)=90 | | 3d-12+5d=8d-12 | | 17cosx-15=0 | | (-2.7)+4.9x=-13.2 | | w-(-8)=-15 | | 2x+6-x=44-15+35 | | 3(x-2)+5=4 | | x^2-4x-7=2cosx |

Equations solver categories